PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BATANG KAPAS PESISIR SELATAN - Kurniati, Wira - (Pendidikan Matematika, 2014)
The background of this research is students have low comrehesion in mathematicconcept at SMPN 2 Batang Kapas, because the students do not want to ask and giveopinion about the material. The purpose of this strategy Giving Question And GettingAnswer is inflvenced on studentsâ comprehensionin mathematic concept at SMPN 2 BatangKapas. This reseach is pre-experimental. Research design is one shot case stud. Thepopulation of this research is students grade eight at SMPN 2 Batang Kapas. Instrument ofthis research is quiz and essay test with realiability is 0,8778. The hyphothesis test isobtained mean value everage studentsâ post test is 65,28 and pre test is 54,58. In condusionGiving Question And Getting Answer active learning strategy is influenced on studentsâcomprehension in mathematic concept at SMPN 2 grade VIII Batang Kapas.